Natural antimicrobial peptides in biomedical applications - Janiszewska, J. (Polimery, 2014)
The paper is an extensive literature review, including the author's work, related to the antimicrobial peptides (AMP). AMP constitute an important element of the immune system of animal and plant organisms. These natural polymers show a broad spectrum of biocidal activity against bacterial, fungal and viral pathogens as well as parasites. The review presents the current classification of AMP peptides and discusses the mechanisms of biological activity. In recent years, several AMP and their analogues have been advanced into clinical development. Special emphasis was put on the antimicrobial activity of dendrimeric peptides and their possible application in medicine.